Adapting measures of social climate for use with individuals with intellectual developmental disability in forensic settings. Issue 4 (21st April 2018) - Bell, Natalie; Tonkin, Matthew; Chester, Verity; Craig, Leam
ABSTRACT: The social climate of forensic settings is thought to impact on a number of important clinical and organisational outcomes and is, therefore, an important construct in relation to the successful functioning of forensic units. A variety of self-report questionnaires have been developed to objectively measure the social climate of forensic settings (e.g. the Correctional Institutions Environment Scale and the Essen Climate Evaluation Schema), however these questionnaires have not been validated for individuals with intellectual developmental disabilities (IDD). Given the prevalence of IDD in prison and forensic psychiatric settings and the potential impact of such cognitive deficits on the ability to complete a range of self-report questionnaires, it is important to consider the potential reliability and validity of existing social climate measures in IDD populations. This article will, therefore: (1) examine the cognitive, linguistic and response format difficulties that may arise when administering self-report measures of social climate in IDD populations; (2) consider potential adaptations to existing measures of social climate that might make them more suitable for use with IDD populations; and (3) identify important directions for future research in the area.